Curriculum Development Management in Media Officer Activities in Pondok Pesantren An-Nidhom Cirebon City - Yesi Aristin; Taqiyuddin Taqiyuddin; Mukhlisoh Mukhlisoh (IAIN Syekh Nurjati Cirebon, 2023)
Managing an educational institution is necessary so that the implementation of education can be run well and is structured. The curriculum is used as a reference in the learning process for more directed practice. Cirebon City An-Nidhom Islamic Boarding School is a non-formal Islamic educational institution that uses the